Different types of headache in patients with systemic lupus erythematosus. (4th May 2015) - Badry, Reda; Gamal, Rania M.
<x xml:space="preserve">Abstract</x> Background: Headache in patients with systemic lupus erythematosus (SLE) is considered a common neurological finding, although the relationship is unclear. Aim: In this study, we aimed to evaluate frequency and characteristics of different types of headache in patients with SLE. Methods: 40 SLE patients were chosen from those referred to the out patient clinic using the American College of Rheumatology (ACR) criteria for the diagnosis of SLE. Headache classification was done regarding the ICD-II criteria in the patients. Headache severity was assessed by visual analog scale (VAS), and subjects with VAS ≥4 were included in the study. Results: 30 patients out of 40 SLE patients (75%) have different headache types: tension type in 37.5% (n = 15) and migraine in 30% (n = 12), cluster 2.5% (n = 1), and intracranial hypertension 5% (n = 2) of all patients. Conclusion: Headache is frequent in SLE especially tension and migraine types, but overall, it is not associated with disease activity.